PEMBUATAN MINUMAN SARI TEMPE DENGAN EKSTRAK JERUK SIAM (Citrus Nobilis) DITINJAU DARI MUTU ORGANOLEPTIK KADAR VITAMIN C DAN KADAR AKTIVITAS ANTIOKSIDAN ISOFLAVON - Kharisma Purry, Ajeng Pridya; Rafiony, Ayu (Pontianak Nutrition Journal, 2018)
Tempe is a processed soy product that has been experiencing a decline in odor as a result of fermentation. Tempe juice beverage is one example of product diversification of food products based on tempe. Siam is one of the local fruits that are quite popular by the community and become the main commodity in West Kalimantan. In the process of making tempe juice, need to add a stabilizer CMC (Carboxy methyl cellulose) as much as 0.25% to produce quality tempe juice. The purpose of this research is to know the making of tempe juice extract with orange extract of siam (citrus nobilis) in terms of organoleptic quality, vitamin C level and isoflavone antioxidant activity level. The research method used experiment with 3 treatment of Siam orange extract 30%, 40% and 50%. The panelists used in the study were slightly trained panelists totaling 25 people. Based on statistical test, there is no effect of making tempe juice with orange extract (citrus nobilis) in terms of organoleptic quality based on color, flavor and taste. Due to the color -0.10 <3.23, the aroma is 2.42 <3.23 and the flavor is 0.17 <3.23. The results of this research is the addition of 50% more siam orange extract can be accepted by panelists. The results of this beverage viscosity were 30% concentration 0.40 dpas, 40% 0.34 dpas and 50% 0.32 dpas. Vitamin test results showed vitamin C content in tempe juice is 56.556 mg / 250 ml sample. Based on the results of isoflavone antioxidant activity test showed antioxidant levels 23%. Can be recommended as one of the beverages that contain antioxidants and vitamin C to meet the needs of the day and need to do further research on the storage power of tempe juice with the addition of orange extract.